Investigation of Aspartate Aminotransferase and Alanine Aminotransferase Detection on Paper-Based Analytical Devices with Inkjet Printer-Sprayed Reagents - Hsiang-Li Wang; Chien-Hung Chu; Sing-Jyun Tsai; Ruey-Jen Yang (New Innovations in Chemistry and Biochemistry Vol. 7, 2022)
General biochemistry detection on paper-based microanalytical devices (PADs) uses pipette titration. However, such an approach is extremely time-consuming for large-scale detection processes. Furthermore, while automated methods are available for increasing the efficiency of large-scale PAD production, the related equipment is very expensive. Accordingly, this study proposes a low-cost method for PAD manufacture, in which the reagent is applied using a modified inkjet printer. The optimal reaction times for the detection of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) are shown to be 6 and 7 min, respectively, given AST and ALT concentrations in the range of 5.4 to 91.2 U/L (R2 = 0.9932) and 5.38 to 86.1 U/L (R2 = 0.9944). The experimental results obtained using the proposed PADs for the concentration detection of AST and ALT in real human blood serum samples are found to be in good agreement with those obtained using a traditional spectrophotometric detection method by National Cheng Kung University hospital.